Effectiveness of a program to lower unwanted media screens among 2–5-year-old children: a randomized controlled trial - Kaur, Nimran; Gupta, Madhu; Chakrapani, Venkatesan; Khan, Firoz; Malhi, Prahbhjot; Kiran, Tanvi; Grover, Sandeep (Frontiers in Public Health, 2024)
Background Limited interventions exist on reducing unwanted screen time (ST) among children from low- and middle-income countries (LMICs), so we developed and assessed the effectiveness of the program to lower unwanted media screen time (PLUMS) among children aged 2–5 years in Chandigarh, Union Territory, North India. Methods An open-label randomized control parallel group trial per CONSORT guidelines was conducted among randomly selected 340 families with children aged 2–5 (±3 months) years in Chandigarh, India. PLUMS was implemented at the family level with a focus on modifying the home media environment and targeted individual-level interventions using parent and child modules for 2 months. A post-intervention (immediately) and a follow-up assessment after 6 months was done. During the follow-up period, the interaction was done passively via WhatsApp groups. The control group received routine healthcare services. Validated and standardized tools, including a digital screen exposure questionnaire with a physical activity component, preschool child behavior checklist, and sleep disturbance scale for children, were used to collect data at baseline, post-intervention, and follow-up periods. The primary outcome was the mean difference in ST (minutes/day) among children in the intervention group versus the control group. Generalized estimating equation (GEE) analysis was performed to adjust for clustering. Results An equal number of families (n = 170) were randomly assigned to the intervention and control arms. In the post-intervention assessment, 161 and 166 families continued while, at the follow-up assessment, 154 and 147 were in the intervention and control arm, respectively. The mean difference in ST on a typical day [27.7 min, 95% Confidence Interval (CI) 5.1, 50.3] at the post-intervention assessment significantly (p < 0.05) decreased in the intervention (102.6 ± 98.5 min) arm as compared with the control (130.3 ± 112.8 min) arm. A significant reduction in ST (β = −35.81 min, CI -70.6, −1.04) from baseline (β = 123.1 min) to follow-up phase (β = 116 min) was observed in GEE analysis. The duration of physical activity increased both at post-intervention (β = 48.4 min, CI = +6.6, +90.3) and follow-up (β = 73.4 min, CI = 36.2, 110.5) assessments in the intervention arm. Conclusion The PLUMS intervention significantly reduced the children’s mean ST on a typical day and increased the physical activity immediately post-intervention and during the 6-month follow-up period. These results might guide the policymakers to include strategies in the national child health programs in the Southeast Asia Region to reduce unwanted ST. Clinical trial registration: https://clinicaltrials.gov/, identifier CTRI/2017/09/009761.